ON THE STUDY OF THE FORMS OF THE MYTHOLOGICAL PROSE OF THE XX CENTURY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the scientific works of scientists, attempts have been made repeatedly to classify the various forms of using the myth in fiction. Our article is the abstracts of a monograph, in which, based on their concepts, we tried to substantiate our own classification of types of mythologism in literature and illustrate it with the achievements of not only Russian, but also national literature.